The Influence of Organizational Support and Work Motivation on Organizational Citizenship Behavior (OCB) Through Work Engagement: Empirical Evidence from Indonesia - Faiqotul Himmah, Tri Siswari; Prayekti, Prayekti; Subiyanto, Didik (Universitas Muhammadiyah Pontianak, 2025)
In government organizations, organizational citizenship behavior (OCB) plays an important role in improving employee performance effectiveness. This study aims to examine the influence of organizational support and work motivation on OCB, with work engagement as a mediating variable. The research subjects were employees of the Human Resources Bureau of the Yogyakarta Regional Police, using a census method and a Likert scale. Data analysis was conducted using PLS-SEM. The results show that work motivation has a positive influence on OCB. Organizational support and work motivation also positively affect work engagement, which in turn mediates their influence on OCB. However, organizational support does not directly affect OCB. These findings have both theoretical and practical significance.